2014
DOI: 10.1080/14330237.2014.978087
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of student burnout and engagement among university students

Abstract: This study investigated influences of core self-evaluation traits, career decision-making difficulties and social support on student burnout and engagement. A cross-sectional design was used with a non-probability quota sample. In the multiple regression analyses, self-efficacy, inconsistent information due to internal conflict and (lack of) parental support were significant predictors of exhaustion, cynicism, vigour and dedication. Self-esteem was also a significant predictor for the two engagement dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
2
25
0
3
Order By: Relevance
“…Learner support should cover assistance in helping students identify specific reasons for their study (Xiao, 2012), become more aware of their own career interests and how these fit in with their studies, and the payoffs and benefits in pursuing and successfully completing their studies in a particular course or programme. Olwage (2012) found that students' sense of dedication was significantly associated with the availability of information about occupations, self-awareness, and the information-gathering and decision-making process. Students perceiving that their studies make sense on an emotional and cognitive level may consequently be more motivated, and generally, more willing to dedicate their energy and effort to deal with perceived difficulties (such as writing an examination).…”
Section: Conclusion and Implications For Practicementioning
confidence: 97%
See 1 more Smart Citation
“…Learner support should cover assistance in helping students identify specific reasons for their study (Xiao, 2012), become more aware of their own career interests and how these fit in with their studies, and the payoffs and benefits in pursuing and successfully completing their studies in a particular course or programme. Olwage (2012) found that students' sense of dedication was significantly associated with the availability of information about occupations, self-awareness, and the information-gathering and decision-making process. Students perceiving that their studies make sense on an emotional and cognitive level may consequently be more motivated, and generally, more willing to dedicate their energy and effort to deal with perceived difficulties (such as writing an examination).…”
Section: Conclusion and Implications For Practicementioning
confidence: 97%
“…In line with the reasoning of the research literature, we propose that positive thoughts about one's studies relate to the efficacy beliefs in one's ability to successfully pursue study activities (such as writing the examination) and one's perceived employability. Positive self-efficacy beliefs are shown to link empirically to stronger career exploration (and study) plans and employability satisfaction (Austin & Cilliers, 2011;Ochs & Roessler, 2004) and study engagement (Olwage, 2012). As self-efficacy reliably predicts the scope of career options considered, occupational interests, career decision-making, perseverance in difficult fields and personal effectiveness, it has been related to the pursuit of entrepreneurial activity and employability satisfaction (Markman, Balkin, & Baron, 2002;Olwage, 2012).…”
Section: Self-efficacymentioning
confidence: 99%
“…Within the pressure of increasing extrinsic demands and personal goals, students' motivation becomes tested (Reiss, 2012). At its worst, bewilderment can result in dropping out of education Stratton, O'Toole, & Wetzel, 2008) or in fatigue (Galbraith & Merrill, 2015;Olwage & Mostert, 2014).…”
Section: Part 2 Successful University Studentsmentioning
confidence: 99%
“…It has been noted that prompt, timely help and support (instead of keeping students dwelling with their concerns) are important conditions of timely graduation . If students believe that their worries are nullified, that they do not dare to bother the teaching personnel with their questions, or that they are ignored, even the smallest issues that could be solved easily can accumulate into big problems and lead to prolonged studies and even dropping out Olwage & Mostert, 2014;Stratton, O'Toole, & Wetzel, 2008).…”
Section: New Friends Are Worth Their Weight In Goldmentioning
confidence: 99%
“…Research has revealed that students' motivation, beliefs, self-efficacy and engagement have a profound impact on their learning, performance and retention (ChanLin, 2009;Hartnett, 2012;Keller, 2008;Olwage, 2012;Roos, 2012;Viljoen, 2012;Xiao, 2012). Actively engaged students who have a strong sense of self-efficacy have been shown to be more productive, motivated, resilient and successful (Olwage, 2012;Roos, 2012). However, there seems to be a paucity of research on how ODL students' life orientation or general attitude toward the world and their work and personal lives influence their study engagement and self-efficacy.…”
Section: Students's Personal Resourcesmentioning
confidence: 99%